My darling Clementine [videorecording (DVD)] - Hellman, Sam (Criterion collection, 2014)
Wyatt Earp is the sturdy lawman who sets about the task of shaping up the disorderly Arizona town of Tombstone, with the help of the boozy, tubercular gambler and gunman Doc Holliday. Though initially at cross-purposes, the pair ultimately team up to confront the violent Clanton gang.